2019
DOI: 10.1016/j.scitotenv.2018.10.032
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach to highlight biological responses of Pisum sativum root to nano-TiO2 exposure in a biosolid-amended agricultural soil

Abstract: This study focused on crop plant response to a simultaneous exposure to biosolid and TiO at micro-and nano-scale, being biosolid one of the major sink of TiO 2 nanoparticles released into the soil environment. We settled an experimental design as much as possible realistic, at microcosm scale, using the crop Pisum sativum. This experimental design supported the hypotheses that the presence of biosolid in the farming soil might influence plant growth and metabolism and that, after TiO 2 spiking, the different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 55 publications
5
22
0
Order By: Relevance
“…In tomato fruits, soil amended with sewage sludge containing TiO 2 NPs increased growth and yield with few changes in the elemental composition and non-altered the biochemical responses [ 17 ]. On the other hand, some negative effects were recently reported: in Pisum sativum and Lens culinaris , oxidative stress [ 18 , 19 ] and imbalance in the mineral nutrition [ 20 ]; in wheat crop, altered metabolism [ 21 ], in barley, delay in reaching the physiological maturity [ 22 ]; in Allium sativum , Lens culinaris and Vicia faba , phyto- and genotoxicity [ 3 , 19 , 23 ]. Toxicity and benefits of TiO 2 NPs are thus not only associated with size, but also with concentration [ 24 ], and plant species [ 25 ] in addition to the properties of receiving soils, which may influence the in-situ TiO 2 processes and induce changes in NPs’ bioavailability and bioactivity [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In tomato fruits, soil amended with sewage sludge containing TiO 2 NPs increased growth and yield with few changes in the elemental composition and non-altered the biochemical responses [ 17 ]. On the other hand, some negative effects were recently reported: in Pisum sativum and Lens culinaris , oxidative stress [ 18 , 19 ] and imbalance in the mineral nutrition [ 20 ]; in wheat crop, altered metabolism [ 21 ], in barley, delay in reaching the physiological maturity [ 22 ]; in Allium sativum , Lens culinaris and Vicia faba , phyto- and genotoxicity [ 3 , 19 , 23 ]. Toxicity and benefits of TiO 2 NPs are thus not only associated with size, but also with concentration [ 24 ], and plant species [ 25 ] in addition to the properties of receiving soils, which may influence the in-situ TiO 2 processes and induce changes in NPs’ bioavailability and bioactivity [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the complex system Bs-soil-plant was impacted by the presence of TiO 2 NPs, inducing negative threats to the quality of both soil and P. sativum plants [ 18 , 20 ]. In these studies, the experimental design was conceived to represent real scenarios of best- and worst-case load of NPs (80 and 800 mg TiO 2 per Kg of soil) through Bs-amended farm soils [ 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…TiO 2 compounds are also able to increase photosynthetic efficiency in plants (Khater, 2015;Giorgetti et al, 2019). With the advantages possessed by chitosan and TiO 2 in enhancing plant growth, in this study the binding of chitosan-TiO 2 was carried out to become a chitosan-TiO2 composite material.…”
Section: Introductionmentioning
confidence: 99%